1962
DOI: 10.1104/pp.37.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Effects on Fruit Respiration . II. Response of Avocados, Bananas, & Lemons

Abstract: ,Most studies concerning the effects of the gas composition of the atmosphere surrounding fruit have been directed toward the response of the combined changes of oxygen (3) is suggested.For the avocado, a fruit which exhibits a climacteric pattern of respiration, it was shown by Biale (2) that low oxygen reduced the respiratory activity during the preclimacteric period andl the (luration of the preclimacteric period was prolonged. Within the range of 2.5 to 21 % oxygen the time required to reach the climact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1963
1963
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…However, strong inhibitions of mitochondrial reactions have been observed only at CO2 concentrations which are considerably higher than those which existed in the present study (9,11). More relevant are the studies of Young et al (14) on the effects of 02 and CO2 levels on the climacteric of intact fruits of several species. Their data show a marked delay of the climacteric in the presence of 10% 02 and 5% CO2 compared to air controls.…”
Section: Aeration Effect On Climacteric and Ripeningmentioning
confidence: 57%
“…However, strong inhibitions of mitochondrial reactions have been observed only at CO2 concentrations which are considerably higher than those which existed in the present study (9,11). More relevant are the studies of Young et al (14) on the effects of 02 and CO2 levels on the climacteric of intact fruits of several species. Their data show a marked delay of the climacteric in the presence of 10% 02 and 5% CO2 compared to air controls.…”
Section: Aeration Effect On Climacteric and Ripeningmentioning
confidence: 57%
“…A paramagnetic 02 analyser has been used to measure 02 uptake by Young and Biale (10,11) with the assay done under 10% CO2 conditions in various kinds of fruit. Lougheed and Franklin (8) report on the use of a infrared CO2 analyser for the measurement of respira- There have been no reports of a device like our system with the ability to measure 02 uptake, CO2 output, and C2H4 evolution simultaneously even under an atmosphere containing a significant amount of any these gases.…”
Section: Resultsmentioning
confidence: 99%
“…High CO.. concentration in the external atmosplhere was shown to retard the climacteric an'd the ripening of several fruits (12,14,27). At the enzymnatic level it was reported that 10 % CO., inhibite(d markedly succinate oxidation (1,17) and phosphoenolpyruvate carboxylase activity (23).…”
Section: Discussionmentioning
confidence: 99%